Do the various radiations present in BNCT act synergistically? Cell survival experiments in mixed alpha-particle and gamma-ray fields. - Phoenix, B; Green, S; Hill, M; Jones, B; Mill, A; Stevens, D (2009)
In many radiotherapy situations patients are exposed to mixed field radiation. In particular in BNCT, as with all neutron beam exposures, a significant fraction of the dose is contributed by low LET gamma ray photons. The components of such a mixed field may show a synergistic interaction and produce a greater cell kill effect than would be anticipated from the independent action of the different radiation types. Such a synergy would have important implications for treatment planning and in the interpretation of clinical results. An irradiation setup has been created at the Medical Research Council in Harwell to allow simultaneous irradiation of cells by cobalt-60 gamma rays and plutonium-238 alpha-particles. The setup allows for variation of dose and dose rates for both sources along with variation of the alpha particle energy. A series of cell survival assays for this mixed field have been carried out using V79-4 cells and compared to exposures to the individual components of the field under identical conditions. In the experimental setup described no significant synergistic effect was observed.